ACGME Interventional Cardiology Milestones 2.0–an overview: Endorsed by the Accreditation Council for Graduate Medical Education. Issue 3 (28th October 2021) - Ijioma, Nkechinyere N.; Don, Creighton; Arora, Vishal; Edgar, Laura; Hawkins, Beau; Monteleone, Peter; Tcheng, James E.; Helmy, Tarek
Abstract: This document provides an overview of the rationale, development, interpretation, and practical suggestions for implementation of the new Accreditation Council for Graduate Medical Education (ACGME) Interventional Cardiology (IC) Milestones 2.0. Previously, IC programs used the general ACGME Milestones for internal medicine. The IC Milestones version 2.0 updates the ACGME competencies to be specific to training in IC. In 2019 an ACGME working group consisting of IC program directors, a lay representative, and representatives from the American Board of Internal Medicine met to develop the IC Milestones version 2.0. The ACGME IC Milestones 2.0 establishes a framework for formative feedback for trainees within domains of patient care, medical knowledge, systems‐based practice, practice‐based learning and improvement, professionalism, and interpersonal and communication skills. The 2021 IC Milestones 2.0 provides a framework for IC mentors and trainees to identify areas for improvement or commendation help stimulate meaningful educational discussions, and provide the basis for self‐reflection and self‐improvement.